Estimated biomass of demersal flshes off Saurashtra coast - Vivekanandan, E; Gopal, C (Indian Journal of Fisheries, 2011)
Trawl survey conducted at regular inter*vals for a long period provides valuable informationon the status of the biomass and spatialand groupwise distribution of fishes, thuis enablingformulation of fishery managementpolicies. There are only a few attempts toestimate the fish biomass of the nordiwestcoast of India (Bapat et al. 1982, Rao andKunjipalu 1989). An analysis was, thaÂ«fore,done to strengthen the existing knowledge onthe demersal fish bicMniass along theSaurashtra coast